Effects of neonatal exposure to bisphenol A on steroid regulation of vascular endothelial growth factor expression and endothelial cell proliferation in the adult rat uterus - Bosquiazzo, Veronica Lis (2010)
Hormonally controlled vascular changes play a key role in endometrial development and in the differentiation process necessary for implantation. Vascular endothelial growth factor (VEGF) has emerged as one of the central regulators of the uterine vasculature. Hormonal perturbations during neonatal development may alter sex steroid-dependent regulation of VEGF and may ultimately affect fertility later in life. The aim of this study was to determine whether neonatal exposure to the environmental estrogenic chemical bisphenol A (BPA) affects the adult rat uterine response to hormonal stimuli. Newborn female rats were given s.c. injections of vehicle, BPA (0.05 mg/kg per day or 20 mg/kg per day) or diethylstilbestrol (0.2 μg/kg per day) on Postnatal Days 1, 3, 5, and 7. To evaluate the long-term effects, rats were ovariectomized at Postnatal Day 80 and submitted to hormonal replacement. Rats neonatally exposed to xenoestrogens showed a decreased induction of uterine endothelial proliferation and a decreased Vegf mRNA expression in response to ovarian steroid treatment. Also, although the estrogen receptor alpha (ESR1) expression was lower in subepithelial cells than in controls, a higher expression of silencing mediator of retinoic acid and thyroid hormone receptor (NCOR1, also known as SMRT) corepressor was evidenced in the same compartment. The results indicate that disturbed Vegf expression in BPA rats could be the result of changes in endocrine pathways, such as an altered induction of ESR1 and/or NCOR1 expression. Because of the importance of VEGF in the implantation process, our data suggest that neonatal BPA exposure might have negative consequences on female fertility.